Estimation of Shrinkage and Dimensional Inaccuracy in Typical Surfaces Produces by FDM - Rumpaul, Ish Kumar (My University, 2018)
A product with good accuracy and strength is always considered as a product of better quality. Accuracy and the strength are always the essential attributes in various RP processes. FDM printing is relatively a typical RP technology which works on the principle of stacking one layer to another to construct a part. In FDM complexity of the part is not a hurdle but there are limitations in every manufacturing process. Accuracy and strength are the attributes which are directly influenced by process parameters. The main initiate of this study is to develop the process planning guidelines to enhance the accuracy of the part fabricated by FDM. Study includes the effect of shrinkage on part manufactured by Reverse Engineering. In Experimentation, shrinkage compensation factor is developed to overcome the shrinkage occurred due to phase change of the material. SCF is been developed on the base of mean method to improve the accuracy of the part. Design of process planning for enhancement of accuracy of the part is also been studied through various experiments. Guidelines were established and confirmed by fabricating parts consisting shrinkage compensation factor. The expected quality of the parts fabricated are counted for each guideline. The outcome of the present research would be fruitful for both the process planner and product designer to manufacture parts by FDM.
Keywords: Design of Manufacturing; Reverse Engineering; Shrinkage Compensation Factor; Fused Deposition Modeling; Accuracy